Assessment of the Effect of 3% Diclofenac Sodium on Photodamaged Skin by Means of Reflectance Confocal Microscopy - Gonzalo Segurado-Miravalles; Natalia Jiménez-Gómez; Oscar Muñoz Moreno-Arrones; Ivette Alarcón-Salazar; Adrian Alegre-Sánchez; David Saceda-Corralo; Pedro Jaén-Olasolo; Salvador González-Rodríguez (Medical Journals Sweden, 2018)
Treatment of actinic keratosis with 3% diclofenac sodium w/w in hyaluronic acid is associated with a concomitant improvement in signs of photodamaged skin. However this effect has not yet been examined in depth. Twenty patients with actinic keratosis and signs of photodamaged skin were studied. They received treatment with diclofenac sodium w/w in hyaluronic acid for 2 months. Clinical and reflectance confocal microscopy assessment on signs of photodamaged skin were performed. Regarding reflectance confocal microscopy, the most common descriptors were: irregular honeycomb pattern in 18/20 patients (90%), mottled pigmentation in 17/20 (85%), coarse collagen structures in all patients, and huddled collagen and curled bright structures in 16/20 (77.8%). After treatment, significant improvement in clinical parameters: irregular pigmentation and coarseness, and confocal parameters: irregular honeycomb pattern and mottled pigmentation, were noted. Reflectance confocal microscopy is a useful tool in monitoring changes in photodamaged skin after treatment. The use of diclofenac sodium w/w in hyaluronic acid is associated with an improvement in some clinical and reflectance confocal microscopy parameters of photodamaged skin.